Implementasi Cloud Computing Pada Aplikasi Pantau Jalanku Menggunakan Google Cloud Platform - Salsabila, Syifa; Afwani, Royana; Zubaidi, Ariyan (Bulletin of Computer Science Research, 2024)
?Cloud computing technology is a computing service with many advantages over conventional systems. Cloud Computing is the right solution because access is easy and fast, and can be accessed anywhere using the internet, one of the Cloud Computing services is GCP (Google Cloud Computing) provided by Google. Cloud computing is implemented in the Pantau Jalanku application. Pantau Jalanku is a pothole damage reporting application created using Android so it requires accurate damage detection and location at an easy cost, so the implementation of Google Cloud Computing includes the use of the AI Platform, Maps Platform, and billing. The aim of implementing cloud computing is to replace hardware or servers in the application backend which allows data in the application to run in real time without requiring a physical device. This research produces accurate accuracy for detecting potholes, as well as the location where road damage occurs. This research discusses how to use Cloud Computing by utilizing Google Cloud so that the need for physical devices such as servers is no longer needed so that it can save costs for creating and operating applications..